Pengaruh Keselamatan dan Kesehatan Kerja, Disiplin Kerja terhadap Produktivitas Kerja melalui Motivasi Kerja pada PT. Sarana Utama Adimandiri - Agung Yulianto; Imam Wibowo; Fajar Cahyo Utomo (JURISMA : Jurnal Riset Bisnis & Manajemen, 2025)
This research aims to determine the effect of occupational safety and health, work discipline, on work productivity through work motivation. This research was conducted at a private company with a research sample of 89 respondents. The sampling technique uses a saturated sample technique. The data analysis method uses path analysis. The results of the research show that: 1) there is an influence of occupational safety and health on work motivation, 2) there is an influence of work discipline on work motivation, 3) there is an influence of occupational safety and health on work productivity, 4) there is an influence of work discipline on work productivity, 5 ) there is an influence of work motivation on work productivity, 6) there is no influence of occupational safety and health on work productivity through work motivation, and 7) there is no influence of occupational safety and health on work productivity through work motivation. Work motivation variables can mediate work safety and health variables and work discipline to increase work productivity Keywords: Occupational Safety and Health; Work Discipline; Work Motivation; Work Productivity; Mediation